A unified model for MESFET analysis - Chattopadhyay S.N.; Pal B.B. (My University, 2025)
A unified model for the shallow channel MESFET device has been developed by considering a generalised doping distribution of impurities in the active region. The I-V characteristics, threshold voltage and transconductance are expressed in terms of fabricational and physical parameters for a Si MESFET structure. Plots have been made and compared for the current against the voltage, the threshold voltage against the concentration and the transconductance against the gate-source voltage for three different impurity profiles, namely, Gaussian, erfc and constant doping.